Design and Development of Login Security System Using Radio Frequency Identification - I Gede Sujana Eka Putra; Ni Luh Putu Labasariyani (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
System security is important in information systems to prevent unauthorized users from accessing data. Login system applies security using encrypted passwords stored on RFID cards. This research designed login security system storing encrypted password using MD5 encryption into the Mifare Tag RFID card and equipped NFC reader to read data from RFID Card. By storing encrypted password characters on RFID cards, login system security is stronger and cannot be traced by unauthorized parties to log into systems. Some stage of system design are through study of literature, designing process flow, system algorithms, designing encryption methods and system interfaces, writing card module coding, card reading module coding, implementation, and system testing. The system login applied by scanning RFID card on the NFC reader, if the password on RFID matches then the user successfully logs into the system. Based on the testing of RFID Tag readings, the maximum distance from the reading of RFID Tag cards is up to 7 cm with a reading range of 00 to 300 with a success rate of 100% authentication. By using RFID Tag cards, increase security for logging into the system, because user cannot log in without having a card with the appropriate password.